Effect of User Personality on Efficacy of a Mental Support System Based on Ambient Intelligence: A Case Study - Iwashita, Motoko; Ishida, Kenji; Ishikawa, Makiko (Frontiers in Computer Science, 2021)
One solution supporting a healthy mental state for humans is controlling the environment with ambient intelligence technology. We are developing a mental support system for healthy people that automatically changes environmental conditions, such as sound volume and light color, depending on the user’s mental state, which is monitored according to physiological signals such as sympathetic nerve activity. In our previous basic study under laboratory-controlled conditions, the system was applied to improve the user’s concentration level as they performed calculation tasks. Results indicated that the system improved the task performance, but individual variations existed, with some users improving greatly but others much less. For the future practical application of the system, determining the causes of the variation in efficacy is important. Considering that the brain structure and activity differ according to an individual’s personality, we investigated the relationship between the user’s personality and task performance with our system’s support. The results showed a clear correlation between the extraversion score and task performance. Our study presents an example where the system’s efficacy is sensitive to the user’s personality and indicates the importance of considering the user’s personality when designing a mental support system based on ambient intelligence.